Information and knowledge: an evolutionary framework for information science - Marcia J. Bates (Information Research: An International Electronic Journal)
Background. Many definitions of information, knowledge, and data have been suggested throughout the history of information science. In this article, the objective is to provide definitions that are usable for the physical, biological, and social meanings of the terms, covering the various senses important to our field. Argument. Information 1 is defined as the pattern of organization of matter and energy. Information 2 is defined as some pattern of organization of matter and energy that has been given meaning by a living being. Knowledge is defined as information given meaning and integrated with other contents of understanding. Elaboration. The approach is rooted in an evolutionary framework; that is, modes of information perception, processing, transmission, and storage are seen to have developed as a part of the general evolution of members of the animal kingdom. Brains are expensive for animals to support; consequently, efficient storage, including, particularly, storage at emergent levels-for example, storing the concept of chair, rather than specific memories of all chairs ever seen, is powerful and effective for animals. Conclusion. Thus, rather than being reductionist, the approach taken demonstrates the fundamentally emergent nature of most of what higher animals and human beings, in particular, experience as information.